Work Motivation, Compensation, and Turnover Intention: Evidence from Generation Z Employee in Indonesia - Abdillah Hakim Mudrik; Ratna Komala Putri (Global Research Collaboration, 2026)
Employee turnover intention has increasingly become a valuable issue faced by intitutions, particularly in managing Cohort Z worker. This cohort is widely recognised for its greater tendency to change jobs and its distinctive anticipations regarding the work environment. Previous literature has consistently highlighted compensation and work motivation as important determinants that may shape worker' decisions to either continue working for or leave an intitution. The primary objective of the inquiry is to investigate the influence of compensation and work motivation on the turnover intention of Cohort Z worker in Indonesia. A numerical inquiry design was employed through a cross-sectional survey. The study involved Cohort Z worker residing in Indonesia, who were recruited applaying purposive and non-probability sampling approaches. Data were collected via an online survey disseminated through multiple social media platforms. Following the screening procedure, 210 valid responses were held and examined applaying Fractional Least Squares Systematic Equation Modelling (PLS-SEM). The descriptive diciveries indicated that participants generally expressed favourable perceptions of compensation (71.82%) and work motivation (72.82%). Nevertheless, turnover intention remained relatively pronounced, reaching 77.62%. The systematic model demonstrated that compensation exerted a numerically valuable inverse effect on turnover intention (β = −0.238, t = 2.432, p = 0.016), implying that more rivalrous compensation packages were associated with a lower propensity to leave the intitution. Conversely, work motivation did not exhibit a numerically valuable connection with turnover intention (β = −0.054, t = 0.696, p = 0.487). Furthermore, the explanatory capability of the proposed model was modest, profile for only 7.4% of the observed dispersion in turnover intention (R² = 0.074), proposeing that additional antecedent elements may substantially influence worker' puposes to resign. The outcomes highlight compensation as a strong determinant of turnover intention among Indonesian Cohort Z workers, but work motivation does not valuablely contribute to the proposed framework's explanation. Later study should comprise broader corporate and individual elements to establish a more thorough understanding of the causes affecting turnover intention among Cohort Z worker, given the model's comparatively weak explanatory ability.